Wealth and Insurance Choices: Evidence from U.S. Households - GROPPER, MICHAEL J.; KUHNEN, CAMELIA M. (Journal of Finance, 2025)
ABSTRACT Using administrative data for 63,000 individuals across 2,500,000 person‐month observations, we find that wealthier individuals have better life insurance coverage, controlling for the value of the asset insured, namely, the consumption needs of dependents. This positive wealth‐insurance correlation, which is surprising given the prevailing view that wealth substitutes for insurance, persists after allowing for wealth‐related differences in risk or bequest preferences, pricing, background risk, education, employment, or liquidity constraints. Our findings call for further investigation of this wealth‐coverage correlation but support theories emphasizing the consumption‐smoothing role of insurance across not only states of the world, but also time.